Direct instantaneous torque control strategy for vehicle SRM based on improved convergence rate sliding mode control - Jingbo Wu; Hongyao Wang; Liuxi Li; Yafeng Yang; Zhijun Guo (Scientific Reports)
Abstract Traditional sliding mode control for switched reluctance motors in direct instantaneous torque control suffers from significant chattering and long response times, which limit its application in new energy vehicle drive systems. To address these issues, this paper proposes a direct instantaneous torque control strategy based on an improved convergence rate sliding mode control. Firstly, system state variables are introduced into the traditional sliding mode convergence rate to adjust the rate at which the system approaches the sliding surface, thereby reducing the system response time. Secondly, a continuous piecewise switching function is introduced to suppress the chattering caused by the discontinuity of the sign function when the system crosses the sliding surface. Finally, the effectiveness of the proposed control strategy is verified by establishing a simulation model of an 8/6-pole switched reluctance motors. Simulation results demonstrate that the proposed control strategy effectively suppresses system chattering and enhances the dynamic performance of the system.